Theoretical prediction of pullout strengths for dental and orthopaedic screws with conical profile and buttress threads. (December 2017) - Shih, Kao-Shang; Hou, Sheng-Mou; Lin, Shang-Chih
Highlights: The dental, trauma, and spinal screw groups were used to evaluate the accuracy of the calculated pullout strengths using different formulae. The experimental tests were conducted to compare the measured and calculated pullout strengths. The buttress threads possess significantly higher pullout strength than the triangle and square ones. However, only thread diameter, pitch, and depth are considered and modeled by the existing formulae. Abstract: Background and objective: The pullout strength of a screw is an indicator of how secure bone fragments are being held in place. Such bone-purchasing ability is sensitive to bone quality, thread design, and the pilot hole, and is often evaluated by experimental and numerical methods. Historically, there are some mathematical formulae to simulate the screw withdrawal from the synthetic bone. There are great variations in screw specifications. However, extensive investigation of the correlation between experimental and analytical results has not been reported in literature. Methods: Referring to the literature formulae, this study aims to evaluate the differences in the calculated pullout strengths. The pullout tests of the surgical screws are measured and the sawbone is used as the testing block. The absolute errors and correlation coefficients of the experimental and analytical results are calculated as the comparison baselines of the formulae. Results: The absolute error of the dental, traumatic, and spinal groups are 21.7%, 95.5%, and 37.0%, respectively. For the screws with a conical profile and/or tiny threads, the calculated and measured results are not well correlated. The formulae are not accurate indicators of the pullout strengths of the screws where the design parameters are slightly varied. However, the experimental and numerical results are highly correlated for the cylindrical screws. The pullout strength of a conical screw is higher than that of its counterpart, but all formulae consistently predict the opposite results. In general, the bony purchase of the buttress threads is securer than that of the symmetric thread. Conclusions: An absolute error of up to 51.4% indicates the theoretical results cannot predict the actual value of the pullout strength. Only thread diameter, pitch, and depth are considered in the investigated formulae. The thread profile and shape should be formulated to modify the slippage mechanism at the bone–screw interfaces and simulate the strength change in the squeezed bones, especially for the conical screw.